2005
DOI: 10.1002/app.21415
|View full text |Cite
|
Sign up to set email alerts
|

Cure kinetic study of carbon nanofibers/epoxy composites by isothermal DSC

Abstract: An investigation was carried out into the cure kinetics of carbon nanofibers (CNF)/epoxy composites, composed of tetraglycidyl-4,4Ј-diaminodiphenylmethane (TGDDM) resin and 4,4Ј-diaminodiphenylsulfone (DDS) as a curing agent. The experimental data for both neat system and CNF/epoxy composites revealed an autocatalytic behavior. Analysis of DSC data indicated that the presence of carbon nanofibers had only a negligible effect on the cure kinetics of the epoxy. Kinetic analysis was performed using the phenomenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 31 publications
4
44
0
Order By: Relevance
“…Figure 4 shows the conversions of reaction (") as a function of temperature for neat epoxy and GO/epoxy nanocomposites at a heating rate of 20°C/min. It can be observed that all curves show a sigmoidal form, which indicates that the cure reaction of TGDDM/DDS system is autocatalytic in agreement with our previous studies [17,18]. Consequently, the incorporation of GOs has no influence on the cure reaction mechanism of the TGDDM/DDS system.…”
Section: Effects Of Gos On the Cure Reactionsupporting
confidence: 89%
See 2 more Smart Citations
“…Figure 4 shows the conversions of reaction (") as a function of temperature for neat epoxy and GO/epoxy nanocomposites at a heating rate of 20°C/min. It can be observed that all curves show a sigmoidal form, which indicates that the cure reaction of TGDDM/DDS system is autocatalytic in agreement with our previous studies [17,18]. Consequently, the incorporation of GOs has no influence on the cure reaction mechanism of the TGDDM/DDS system.…”
Section: Effects Of Gos On the Cure Reactionsupporting
confidence: 89%
“…Differential scanning calorimetry (DSC) may be considered as one of the most interesting techniques for kinetic analysis of cure reactions of thermosetting systems [13][14][15]. Numerous studies on cure kinetics of epoxy in presence of carbon-based nanofillers have been investigated [16][17][18][19][20][21][22][23][24][25]. Recently, Allaoui and El Bounia [16] had reviewed the influence of CNTs on the cure kinetics of epoxy resin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of all, the most valuable one is carboxylic acid groups. This is because a number of coupling reactions can take place in the presence of carboxylic acid groups, which enables introduction of different types of chemical molecules onto the surfaces of nanofillers [9,10]. However, chemical functional groups grafted onto the surfaces of nanofillers may have some considerable influences on the features of composite processing.…”
Section: Introductionmentioning
confidence: 99%
“…However, chemical functional groups grafted onto the surfaces of nanofillers may have some considerable influences on the features of composite processing. In particular, they may alter cure kinetics, viscosity and flow behavior of the injected matrix resin in a simultaneous manner [2,[6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%